2014
DOI: 10.1186/s40490-014-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Understorey vegetation gradient in a Eucalyptus grandis plantation between a savanna and a semideciduous forest

Abstract: Background: Plant community assemblage is influenced by many factors, including soil characteristics and the arrival of diaspores from surrounding areas. These factors may be especially important in transition areas, leading to spatial gradients in the plant community. Methods: This study was performed in the understorey of an abandoned Eucalyptus grandis W. Hill ex Maiden plantation between a savanna and a forest, 490 m apart, in south-eastern Brazil. This study assessed whether the spatial variation in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Therefore, incorporating the functional and phylogenetic relatedness of community-forming species may enhance our understanding of the studied community (Cadotte et al, 2010;Swenson, 2013;Magura, 2017). Several recent edge-related studies sought such understanding using functional (Barbaro et al, 2014;Ma & Herzon, 2014), phylogenetic (Dodonov et al, 2014;Peralta et al, 2015), or combined (Luza et al, 2015) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, incorporating the functional and phylogenetic relatedness of community-forming species may enhance our understanding of the studied community (Cadotte et al, 2010;Swenson, 2013;Magura, 2017). Several recent edge-related studies sought such understanding using functional (Barbaro et al, 2014;Ma & Herzon, 2014), phylogenetic (Dodonov et al, 2014;Peralta et al, 2015), or combined (Luza et al, 2015) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…For example, clear cutting and comparatively short rotations favor the occurrence of ruderal plant species (i.e., species able to survive on inhospitable and/or disturbed habitats), whereas some long-lived climax species may not be present [34]. This fact does not occur in the abandonment area due the ceasing of management actions [13].…”
Section: Floristic and Phytosociology Datamentioning
confidence: 99%
“…Tree plantations reduce ecological health compared to natural forests. After tree harvest when the management of such areas changes A c c e p t e d M a n u s c r i p t 4 from production to conservation, ecological restoration techniques may be preferred rather than "doing nothing" to more rapidly return to of the environmental conditions found in adjacent natural forests [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, studies on the natural regeneration in the understory of forests with exotic species have demonstrated that these stands are, most of the times, a biodiversity redoubt (Alencar et al, 2011;Venzke et al, 2012;Dadonov et al, 2014), in which spontaneous native species of the Cerrado can be used as a starting point for restoration actions. On the above, this study aimed to evaluate the natural regeneration of the understory eucalyptus stand and to investigate environmental factors that can be related to the establishment of this vegetation, since this information could subsidy actions and strategies of restauration that consider the use of the natural regeneration.…”
Section: Introductionmentioning
confidence: 99%